EFEKTIFITAS MODEL COOPERATIF LEARNING TYPE TEAM ASSITED INDIVIDUALY (TAI) PADA MATERI TRAPESIUM - Anzora Anzora; Irma Aryani; Rini Susiani (Jurnal Dedikasi Pendidikan, 2022)
One of the learning model that help to develop students’ thinking ability to be more critical and creative in dealing with problems and to improve the students’ understanding of Mathematicalconcept is cooperative learning model type TAI (Team Assisted Individualization).This study aimed to discover the effect of using cooperative learning model type TAI (Team Assisted Individualization) related to trapezoid material.The instruments used in this study were teacher and students observation sheet, questionnaire, interview, Lesson Plan, Students’ Worksheet, Pre-test and Post-test.Futhermore, the result of students achivement data  were analyzed using Minimum Mastery Criterion (MMC), whereas data of teachers competence, students activity, students respond, and students learning outcomes were analyzed using descriptive analysis in terms of rate percentage.Based on the data analysis, the result of the study showed that cooperative learning model type TAI (Team Assisted Individualization) is an effective strategy. The result informed that the teacher’s ability to organize cooperative learning type TAI is effective (indicated by score 4.00), the student’s activity during teaching and learning process based on cooperative learning type TAIn is effective, the exhaustiveness of the students in classical manner is effective (indicated by 83,33 % of the students fulfil the Minimum Mastery Criterion) and more than 80% of the students gave vastly positive response in relation to TAI implementation. It can be inferred that the cooperative learning type TAI (Team Assisted Individualization) is an effective strategy in teaching trapezoid material.